Preparation and characterization of negatively charged PES nanofiltration membrane by blending with halloysite nanotubes grafted with poly (sodium 4-styrenesulfonate) via surface-initiated ATRP - Zhu, J.; Guo, N.; Zhang, Y.; Yu, L.; Liu, Jian (Elsevier BV, 2014)
Sodium 4-styrenesulfonate was grafted onto the surfaces of halloysite nanotubes (HNTs) via surface-initiated atom transfer radical polymerization (SI-ATRP), and then negatively charged nanofiltration (NF) membranes were fabricated by blending various contents of HNTs-poly(sodium 4-styrenesulfonate) (HNTs-poly(NASS)) composites via phase inversion method. The grafting degree was effectively controlled by varying the reaction time and the amount of monomers. The results of FT-IR, TGA, and TEM indicated that HNTs-poly (NASS) composites were successfully synthesized and GPC results exhibited the linear relationship between number-average molecular mass (Mn) and reaction time. In addition, the membranes were characterized by SEM, static water contact angle and water ratio. It was found that the hydrophilicity of hybrid membranes was significantly superior to bare PES membranes, which corresponded to the results of pure water flux and thus may enhance fouling resistance to a certain extent. The ion-exchange capacity (IEC) value could be up to 0.07. mmol/g when the HNTs-poly (NASS) content was only 3. wt%. Meanwhile, the pure water flux of the hybrid membranes increased with increasing the HNTs-poly (NASS) content. The permeation ratio for saline solution increased significantly, such as P(MgCl2) from 77% to 96.5%. From the analysis above, these prepared hybrid membranes have a potential application in desalination of textile industry and wastewater treatment. © 2014 Elsevier B.V.